2018
DOI: 10.1159/000489455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamisoyo-San Decoction, a Traditional Chinese Medicine, on Gastrointestinal Motility

Abstract: Background: Gamisoyo-San decoction (GSS), a traditional Chinese medicine, has been used to treat various gastrointestinal (GI) symptoms and diseases such as functional dyspepsia. The purpose of this study was to investigate the effect of GSS on GI motility functions in mice. Methods: Percent intestinal transit rate (ITR%) and gastric emptying (GE) values were measured using Evans Blue and phenol red, respectively, in normal mice and in mice with experimentally induced GI motility dysfunction (GMD). Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Traditional herbal medicine has been listed as a second-line treatment in the guidelines of the Japanese Society of Gastroenterology, although with weak recommendations ( 6 ). The Jiawei Xiaoyao (JX) pill, which contains the same components as Gamisoyo-San in Japan ( 13 ), is an herbal medicine that is broadly used throughout China, Japan, and Korea to promote Qi and blood as well as to nourish the spleen based on the framework of traditional medicine theory; it also relieves symptoms such as epigastric discomfort ( 14 ). The 6-g JX pill is composed of the following raw herbs: Paeonia lactiflora Pall., 1.8 g; Atractylodes macrocephala Koidz., 1.8 g; Mentha canadensis L., 0.36 g; Bupleurum falcatum L., 1.8 g; Angelica sinensis (Oliv.)…”
Section: Introductionmentioning
confidence: 99%
“…Traditional herbal medicine has been listed as a second-line treatment in the guidelines of the Japanese Society of Gastroenterology, although with weak recommendations ( 6 ). The Jiawei Xiaoyao (JX) pill, which contains the same components as Gamisoyo-San in Japan ( 13 ), is an herbal medicine that is broadly used throughout China, Japan, and Korea to promote Qi and blood as well as to nourish the spleen based on the framework of traditional medicine theory; it also relieves symptoms such as epigastric discomfort ( 14 ). The 6-g JX pill is composed of the following raw herbs: Paeonia lactiflora Pall., 1.8 g; Atractylodes macrocephala Koidz., 1.8 g; Mentha canadensis L., 0.36 g; Bupleurum falcatum L., 1.8 g; Angelica sinensis (Oliv.)…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the CP dose employed was as reported by Viana-Cardoso et al (2011) and Shin et al (2018); this dose sufficiently induced GE delay by dysautonomia. The dose of MLT was based on previous studies indicating its protective effects (Kasimay et al, 2005;Konturek et al, 2007;Barberino et al, 2017;Kim et al, 2019).…”
Section: Phase I -Effect Of Different Melatonin Doses On Cisplatin-in...mentioning
confidence: 64%
“…Although lots of TCMs showed efficacy for the treatment of gastrointestinal motility disorders, only a few of the underlying mechanisms of these treatments have been explored [49]. Among them, many studies chose to measure the changes in GE during treatment to demonstrate their efficacy [50][51][52]. The feasibility and availability of PET for GE measurement established in this study would provide a powerful tool for these pharmacological studies.…”
Section: Discussionmentioning
confidence: 95%